Correction: Automatic Cyclic Alternating Pattern (CAP) analysis: Local and multi-trace approaches. - Maria Paola Tramonti Fantozzi; Ugo Faraguna; Adrien Ugon; Gastone Ciuti; Andrea Pinna (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0260984.].